Prevalence and Factors Associated with Teenage Pregnancy, Northeast Ethiopia, 2017: A Cross-Sectional Study - Yohannes Ayanaw Habitu; Anteneh Yalew; Telake Azale Bisetegn (Journal of Pregnancy)
Introduction. Though teen age pregnancy had poor maternal and perinatal health outcomes, its magnitude and determinants are not well understood. Therefore, the aim of this study was to assess the prevalence and associated factors of teenage pregnancy in Wogedi, northeast Ethiopia. Methods. A community-based cross-sectional study was conducted among 514 teenagers in Wogedi, northeast Ethiopia, from April to May 2017. Data were collected using a structured questionnaire, entered, and analyzed appropriately. Odds ratios with 95% confidence interval and P-values were computed using appropriate logistic regression models to determine the presence and strength of associations between the dependent and independent variables. Results. The prevalence of teenage pregnancy in Wogedi was 28.6% (95% CI: 24.9, 32.5). Age (AOR=2.10; 95% CI: 1.55, 2.88), rural residence (AOR=3.93; 95% CI: 1.20, 12.83), contraceptive nonuse (AOR=10.62; 95% CI: 5.28, 21.36), and parental marital status (divorce) (AOR=1.98; 95%CI: 1.13, 3.93) were found to have statistically significant associations with teenage pregnancy. Conclusions. There is high prevalence of teenage pregnancy in the area. Age, residence, contraceptive nonuse, and parental divorce were found to have a statistically significant association. Strengthening contraceptive use by giving special attention to rural dwellers and showing the consequences of divorce to the community are strongly recommended.